Performance of Coal Bottom Ash as Partial Cement Replacement in Mortar - Jambri, Saiful Shafiq; Ali, Noorwirdawati (Recent Trends in Civil Engineering and Built Environment, 2023)
Coal bottom ash is the granular by-product of burning coal to create steam and electricity. The amount of coal bottom ash (CBA) produced has increased. Thus, disposal issues arise. Thus, this study sought to investigate the effectiveness of CBA as a partial cement replacement in a mortar and the optimum percentage of CBA in a mortar. The percentage of CBA utilized to substitute cement in the concrete mixture ranges from 10% to 30%. Concrete with CBA as a cement replacement was tested for compressive strength, density, and water absorption. Based on this research, the ideal CBA content for compressive strength and water absorption is 10%. Compression strength tests demonstrated that 10% and 15% of CBA mixtures had surpassed the control specimen at 28 days.